Oral bleeding: a case report of hemangioma of palate - Maharjan, Alisha; Dhungana, Sundar (Journal of General Practice and Emergency Medicine of Nepal, 2023)
Hemangiomas are benign vascular tumors of blood vessels that represent a gray area between hamartomatous malformation and true neoplasms. In spite of being largely benign, they can become unpleasant, disfiguring and also sometimes fatal if they affect vital structures. More than half of the cases occur in head and neck; however, intraoral hemangiomas are relatively rare. They can present in a variety of ways. This is a case report of cavernous hemangioma of hard palate which presented with intra oral bleeding and ulcer, which was initially investigated as being a probable case of neoplastic lesion of the palate in a 71-year-old woman.